ANALISIS KINERJA PENGELOLAAN LINGKUNGAN INDUSTRI DI KAWASAN SIMONGAN KOTA SEMARANG - , Zaenuri, Drs.,SE.,M.Si.Akt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research was conducted in several companies in Simongan Industrial Area of Semarang City. This industrial area had been selected because performances of the companies in the area in 'environmental managements' have become an important focus in accord with the Regional Regulation Number 8, 2004, on Detailed Plans for City-Level Spatial Arrangements for the year period of 2000-2010. This research had several objectives: (1) To analyze the factors having potentials to affect the performances of the companies in environmental managements. (2) To analyze the correlation between eco-efficiencies and performances in environmental managements. (3) To analyze general perceptions of the local communities on the companies' performances in environmental managements This research was designed using an ecological approach and conducted in 9 companies consisting of pharmaceutical, vegetable oil and paving blocks & tile companies (one each) and textile, galvanizing and furniture companies (two each). This research analyzed not the industrial area but the companies in the Area. This research analyzed both primary and secondary data. The primary data covered (1) companies' performances in environmental managements, (2) ecoefficiencies and (3)perceptions of the local communities. The data were analyzed descriptively and inferred using analytical hierarchical processes (AHP), multiple-linear regressions and oneway anova This research produced the following results: (1) The performances of environmental managements were influenced by the company's vissions, missions and quality and environmental policies. The quality and environmental policies constitutes the company's commitment to manage the environment, as implemented by periodically testing the liquid wastes, the ambient air, the gas emissions and noises. These activities reflect a commitment to implement RKL/RPL or UKL/UPL that have already been established. (2) The companies have applied several concepts of eco-efficiencies in their environmental managements. The concept of eco-efficiency was implemented based on the paradigm of entrophy, by which the production processes are improved continuously that the production costs and wastes could be minimized. Externally, the environmentally friendly brands of the companies would be more attractive to international consumers that the access to international markets would be opened more and the sales and profits might be increased. Therefore, the entrophy paradigm, rather than the poison one, for managing the environments, would provide more benefits to the companies. (3) Although several companies in Simongan Area still managed their environments based on poison paradigm, many others have shifted to entrophy paradigm that most of the communities in the Area are able to live comfortably. The interaction between the industries and the communities has become mutual simbiotic in nature. However, there are some members of the communities, particularly those with relatively high incomes and educational backgrounds, who are very critical to companies polluting the air and producing excessive noises. These individuals reported the violations to BLH. Fortunately, these reports were responded positively by the BLH and the managements of the companies in question. It means that the control by the communities run effectively that the performances of the industrial companies in environmental managements become better and better